2012
DOI: 10.1111/j.1744-7402.2012.02817.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Hardness Tests to Quantify Bulk Plasticity and Predict Transition Velocities in SiC Materials

Abstract: It has long been known that a relation exists between a material's hardness and its gross impact performance; however, the nature of this relationship has not been understood to a degree useful in materials development. Many studies have shown that harder ceramics tend to display better ballistic performance. In addition, some research has suggested that a material's potential for inelastic deformation (or its "quasi-plasticity"a bulk property) may also play an important role in its resistance to penetration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…10,11 These values, in combination with hardness, have been shown to correlate with experimentally obtained transition velocities (the impact velocity corresponding to the transition from projectile dwell to penetration) measured by Lundberg and Lundberg. 12 The ability of a ceramic to sustain projectile dwell (i.e.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…10,11 These values, in combination with hardness, have been shown to correlate with experimentally obtained transition velocities (the impact velocity corresponding to the transition from projectile dwell to penetration) measured by Lundberg and Lundberg. 12 The ability of a ceramic to sustain projectile dwell (i.e.…”
Section: Introductionmentioning
confidence: 58%
“…Whilst the validity of predicting transition velocities from indentation is questionable, as acknowledged by the original authors, 11 given the large differences in interaction volume and strain rate, the correlation with ballistic performance further highlights the importance of hardness in defeating AP projectiles and the potential for indentation to be used as a screening method to rank candidate ceramics.…”
Section: Ballistic Performancementioning
confidence: 95%
See 1 more Smart Citation
“…Recent work by Hilton et al . refined this equation and demonstrated that this technique is robust enough to provide accurate estimates of transition velocity for load–hardness data sets acquired by multiple operators on different instruments . Due to the relative ease with which this methodology can be employed, the McCauley Wilantewicz method has been proposed as a possible screening tool for determining the applicability of a ceramic material for specific applications of interest…”
Section: Introductionmentioning
confidence: 99%
“…The methodology employed by McCauley and Hilton uses average hardness values measured at each applied load when applying the power law curve fit whose parameters are critical in estimating transition velocity . The use of averages makes analysis of the certainty of this estimate difficult, as it is unintuitive how the power law parameters vary as a function of the variance present in the load–hardness data set.…”
Section: Introductionmentioning
confidence: 99%